CT Scan Finding Characteristics of Confirmed Covid-19 Patients Based on Clinical Symptom Onset Patterns - Dewi Roziqo; Anita Widyoningroem; Prijambodo; Rosy Setiawati (Indian Journal of Forensic Medicine & Toxicology, 2022)
Chest computed tomography (CT) scan is one of the main modalities to detect COVID-19 infection.Several CT scan findings are the hallmark to rapidly detect suspected COVID-19 infection, thereforetimely treatment could be administered. This study aims to describe chest CT scan findings of confirmedCOVID-19 patients based on clinical symptom onset patterns.This study is a descriptive study with a retrospective design in confirmed COVID-19 patients. Dataregarding characteristics of chest CT scan findings and the patient’s history including clinical symptomsonset were collected.There were 123 subjects in this study. The study data were categorized into modified clinical symptomonset patterns which were early, progressive, peak, absorption, and advanced phases. Most of male(57%) and female (43%) patients that were admitted to the hospital were in absorption phase of thedisease with fever, cough, and dyspnea as the most prevalent symptoms. Chest CT scan findings ofabsorption phase included GGO (ground glass opacity) in 28 patients (76%), crazy paving pattern in18 patients (49%), consolidation in 22 patients (59%), and fibrosis in 31 patients (84%). Chest CT scanfindings of confirmed COVID-19 patients vary depending on the phase of the disease. Risk factors andsecondary bacterial infection may contribute to long-term persistence of symptoms.